Handbook of formative assessment 2026-02-15T16:55:29+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Andrade, Heidi L; Cizek, Gregory J (Routledge, 2010)

(untitled)
Formative assessment refers to a wide variety of information gathering activities used to adapt instruction to the current & future needs of students. Included in these activities are traditional classroom tests, observations, oral questioning, class discussions, group & individual projects, & homework